2014
DOI: 10.1159/000362251
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Mass Progression despite Stable Blood Pressure and Kidney Function in Stage 3 Chronic Kidney Disease

Abstract: Background/Aims: Progressive chronic kidney disease (CKD) is associated with worsening cardiovascular (CV) risk not explained by traditional risk factors. Left ventricular (LV) hypertrophy (LVH) is an important CV risk factor, but its progression has not been documented in early CKD. We explored whether progression of LVH in early CKD would occur despite stable kidney function. Methods: We conducted a post hoc analysis of a 12-month study of lanthanum carbonate in stage 3 CKD, which included longitudinal asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 82 publications
1
26
0
1
Order By: Relevance
“…As Seifert et al [18] have recently reported, patients with stage 3 CKD exhibited increasing left ventricular mass, persistent left ventricular diastolic dysfunction and vascular stiffness, which is consistent with our data. Previous studies have pointed out that Aix and PWV were risk factors for CAD [19,20], while our results also showed a higher occurrence of CAD in patients with high Aix and PWV indexes.…”
Section: Discussionsupporting
confidence: 93%
“…As Seifert et al [18] have recently reported, patients with stage 3 CKD exhibited increasing left ventricular mass, persistent left ventricular diastolic dysfunction and vascular stiffness, which is consistent with our data. Previous studies have pointed out that Aix and PWV were risk factors for CAD [19,20], while our results also showed a higher occurrence of CAD in patients with high Aix and PWV indexes.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we observed no significant increase over time of BP, and no significant change over time in CCA diameter, CIMT, or Ep in the CKD patients. Somehow contradictory to this, a study of 31 patients with Stage 3 CKD observed a progression of LVM over 12 months, despite stable BP and kidney function (Seifert et al, 2014). However, it is possible that the close monitoring of our patients by a dedicated nephrology clinic could have contributed to the lack of progression over time in these cardiovascular parameters.…”
Section: Discussionmentioning
confidence: 63%
“…Biomarkers including an abnormal ankle-brachial index (ABI), arterial stiffness, increased common carotid artery (CCA) diameter and intima-media thickness (CIMT), and left ventricular hypertrophy (LVH) are associated with increased cardiovascular risks and worse prognosis in CKD (Szeto et al, 2007;Chue et al, 2010;Paoletti et al, 2011;Karras et al, 2012;Kozakova et al, 2017;Chen et al, 2017;Major et al, 2018). Moreover, most of the studies of mildto-moderate CKD have evaluated the deterioration of renal function over time (Baek et al, 2012;Hallan et al, 2012), and few have addressed the longitudinal changes in biomarkers associated with cardiovascular risk (Seifert et al, 2014;Agarwal, 2017). Moreover, most of the studies of mildto-moderate CKD have evaluated the deterioration of renal function over time (Baek et al, 2012;Hallan et al, 2012), and few have addressed the longitudinal changes in biomarkers associated with cardiovascular risk (Seifert et al, 2014;Agarwal, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, much attention has been focused on the role of FGF23 since this substance not only participates in the phosphate homeostasis but also induces cardiac hypertrophy (Table 3) [21,22,[118][119][120][121][122]. Thus, Gutierrez et al [21] discovered that there existed a close relationship between serum FGF23 levels and LV mass index in patients with CKD.…”
Section: Fgf23 and Cardiac Hypertrophymentioning
confidence: 99%